Aluminum nitride ceramic slurry, preparation method and application thereof

CN122916684APending Publication Date: 2026-10-16NANCHONG THREE CIRCLE ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610944363.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]然而,现有氧化钇基氧化物烧结助剂体系存在以下技术短板:氧化物助剂的引入会向氮化铝烧结体系中大量引入氧杂质原子,在高温烧结过程中,氧原子极易固溶进入氮化铝晶格内部,取代晶格中的氮原子形成晶格缺陷与杂质空位;同时,过量氧元素会在氮化铝晶界处生成低导热、低强度的钇铝氧晶界相;晶格缺陷与劣质晶界相的协同作用,会大幅加剧电子和声子的散射效应,显著降低氮化铝陶瓷基板的热传导效率;此外,晶界杂相的存在会破坏晶粒结合的完整性与致密性,引发晶界应力集中,弱化晶粒间的结合强度,最终导致氮化铝陶瓷基板的抗弯强度、断裂韧性等机械性能大幅下降,难以兼顾高致密度、高热导率与高强度的综合性能需求

Benefits of technology

[0036]Compared with existing technologies, the beneficial effects of this invention are as follows: First, the aluminum nitride ceramic substrate prepared by this invention using a sintering aid system containing Al-Y alloy exhibits significant improvements in flexural strength, density, and thermal conductivity, while maintaining excellent volume resistivity, achieving synergistic optimization of high thermal conductivity and high strength. Second, the Al-Y alloy in the aluminum nitride ceramic slurry of this invention can more thoroughly purify the aluminum nitride lattice and optimize the distribution of grain boundary phases, thereby obtaining a higher density ceramic body at a lower sintering temperature, with fewer internal pores and better grain bonding. Furthermore, the aluminum nitride ceramic substrate prepared by this invention has excellent comprehensive performance, meeting the stringent requirements of high-power electronic devices for efficient heat dissipation while possessing good mechanical reliability and electrical insulation characteristics. It can be widely used in high-end electronic packaging scenarios such as high-density semiconductor lighting, 5G communication RF modules, and new energy vehicle power devices, significantly improving the long-term operational stability and service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the technical field of electronic ceramic materials, and discloses an aluminum nitride ceramic slurry as well as a preparation method and application thereof.The aluminum nitride ceramic slurry comprises aluminum nitride powder, a sintering aid and an organic aid; the sintering aid comprises an Al-Y alloy; and the mass ratio of Al to Y in the Al-Y alloy is 1:(0.2-5).The aluminum nitride ceramic substrate prepared from the aluminum nitride ceramic slurry has excellent thermal conductivity and bending strength, can realize the synergistic improvement of the thermal conductivity and mechanical properties while maintaining high density and high volume resistivity, meets the harsh requirements of high-power electronic devices on high-efficiency heat dissipation, has good mechanical reliability and electrical insulation characteristics, and can be widely used in high-density semiconductor lighting, 5G communication radio frequency modules, new energy automobile power devices and other high-end electronic packaging scenes, and significantly improves the long-term working stability and service life of electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic ceramic materials technology, specifically to an aluminum nitride ceramic slurry, its preparation method, and its application. Background Technology

[0002] In high-end intelligent manufacturing fields such as semiconductors, 5G communications, and new energy, electronic devices are rapidly iterating and upgrading towards higher integration, higher power density, miniaturization, and higher frequency, resulting in a continuous surge in heat generated during device operation. If this heat cannot be dissipated quickly and efficiently, it will lead to increased operating temperature, decreased operational stability, shortened lifespan, and even equipment failure or damage. As the core heat dissipation and insulation substrate for high-power electronic devices, the thermal conductivity, mechanical properties, electrical insulation properties, and interface compatibility of the heat dissipation substrate directly determine the reliability of the electronic devices. Aluminum nitride (AlN) ceramics, due to their high thermal conductivity, excellent electrical insulation, and good compatibility with semiconductor materials, have become the preferred heat dissipation packaging substrate for high-power, high-frequency electronic devices, and market demand and industrial scale continue to expand.

[0003] However, with the continuous improvement of the performance indicators of high-end electronic devices, the industry's requirements for the comprehensive performance of aluminum nitride ceramic substrates are becoming increasingly stringent. Not only must the substrate possess ultra-high thermal conductivity to meet the demands of rapid heat dissipation, but it must also possess excellent mechanical properties such as bending strength, impact resistance, and density to adapt to precision packaging, surface mount processing, and long-term stable operation under complex conditions. Aluminum nitride itself has inherent physicochemical defects—its crystal structure is dominated by strong covalent bonds, with high bonding energy and strong lattice stability, and its extremely high melting point leads to high sintering activation energy and slow particle diffusion rate. Furthermore, pure-phase aluminum nitride powder is difficult to densify under conventional sintering processes, easily resulting in problems such as high substrate porosity, insufficient density, and uneven grain development. This leads to low thermal conductivity and poor mechanical strength in the finished product, failing to meet the application standards of high-end fields.

[0004] To overcome the technical challenge of sintering aluminum nitride ceramics, the industry commonly employs the introduction of sintering aids to reduce sintering activation energy, improve grain growth kinetics, and achieve low-temperature densification sintering. Currently, rare earth oxides and alkaline earth metal oxides are the most widely used aid systems in aluminum nitride sintering. Among them, yttrium oxide, with its excellent sintering activity and suitable eutectic temperature range, can effectively refine grains, promote grain boundary slip, and eliminate porosity, making it a core sintering aid for the large-scale preparation of aluminum nitride ceramic substrates.

[0005] However, existing yttrium oxide-based oxide sintering aid systems have the following technical shortcomings: the introduction of oxide aids introduces a large number of oxygen impurity atoms into the aluminum nitride sintering system. During high-temperature sintering, oxygen atoms readily dissolve into the aluminum nitride lattice, replacing nitrogen atoms in the lattice and forming lattice defects and impurity vacancies. At the same time, excess oxygen will generate low thermal conductivity and low strength yttrium aluminum oxide grain boundary phases at the aluminum nitride grain boundaries. The synergistic effect of lattice defects and inferior grain boundary phases will significantly aggravate the scattering effect of electrons and phonons, significantly reducing the thermal conductivity of aluminum nitride ceramic substrates. In addition, the presence of grain boundary impurity phases will destroy the integrity and compactness of grain bonding, causing grain boundary stress concentration, weakening the bonding strength between grains, and ultimately leading to a significant decrease in the mechanical properties of aluminum nitride ceramic substrates such as bending strength and fracture toughness, making it difficult to meet the comprehensive performance requirements of high density, high thermal conductivity, and high strength.

[0006] Therefore, there is an urgent need to develop an aluminum nitride ceramic slurry and preparation process that can effectively avoid oxygen impurity defects and simultaneously improve the thermal conductivity and mechanical properties of the substrate, so as to meet the stringent requirements of the high-end electronic device field for high-performance aluminum nitride heat dissipation substrates. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide an aluminum nitride ceramic slurry, its preparation method, and its application.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides an aluminum nitride ceramic slurry, comprising aluminum nitride powder, a sintering aid, and an organic additive; wherein the sintering aid comprises an Al-Y alloy; wherein the mass ratio of Al to Y in the Al-Y alloy is 1:(0.2-5).

[0009] This invention utilizes a pre-alloyed Al-Y alloy to replace traditional oxides as the core sintering aid, constructing a novel low-oxygen, high-activity sintering system that achieves a synergistic leap in the thermal conductivity and mechanical properties of aluminum nitride ceramics. Specifically, when the Al-Y alloy of this invention reacts with the oxygen components in the aluminum nitride ceramic slurry and the residual oxygen in the subsequent sintering atmosphere, it effectively reduces and removes impurity oxygen atoms from the aluminum nitride lattice, achieving deep lattice purification and significantly reducing phonon scattering, thus creating conditions for achieving high thermal conductivity. Secondly, unlike traditional oxide sintering aids or simple metal mixtures, the Al-Y alloy of this invention is introduced in a pre-alloyed form, allowing Al and Y elements to achieve uniform distribution at the microscale. During sintering, these elements can participate in the reaction simultaneously and fully, forming a uniform and fine Y-Al-ON liquid secondary phase. This liquid phase promotes the densification of the ceramic through particle rearrangement and dissolution-precipitation mechanisms, and its uniform distribution at grain boundaries avoids structural defects caused by local enrichment or absence, thereby effectively strengthening grain boundaries and improving the mechanical strength of the material. Furthermore, the Al-Y alloy of the present invention has a lower melting point than elemental Y, which is beneficial for initiating liquid phase sintering at a lower temperature, and the alloy liquid has better wettability relative to aluminum nitride ceramics, further enhancing sintering activity.

[0010] In a preferred embodiment of the aluminum nitride ceramic slurry of the present invention, the mass ratio of Al to Y in the Al-Y alloy is 1:(1.5-5).

[0011] In the aluminum nitride ceramic slurry of the present invention, when the mass ratio of Al to Y in the Al-Y alloy is within the above range, it can more fully exert its role in "oxygen absorption" and "crystal lattice purification". At the same time, the Y-based grain boundary phase formed is more continuous and has lower thermal resistance, thereby achieving a better balance in thermal conductivity and mechanical properties.

[0012] Preferably, in the Al-Y alloy, the mass ratio of Al to Y is one or a combination of 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, and 1:5.

[0013] As a preferred embodiment of the aluminum nitride ceramic slurry of the present invention, the Al-Y alloy is formed by mixing Al metal and Y metal, performing vacuum induction melting, and then ball milling in a high-purity argon atmosphere.

[0014] In the aluminum nitride ceramic slurry of this invention, the Al-Y alloy is formed by mixing Al metal and Y metal, followed by vacuum induction melting and ball milling in a high-purity argon atmosphere. This ensures that Al and Y form a uniform intermetallic compound at the microscale, avoiding component segregation caused by simple mechanical mixing, and guaranteeing the uniformity and stability of sintering activity.

[0015] As a preferred embodiment of the aluminum nitride ceramic slurry of the present invention, the mass ratio of the aluminum nitride powder to the Al-Y alloy is 1:(0.01-0.5); and / or, the sintering aid further includes CaO and Li2O; the mass ratio of the Al-Y alloy, CaO, and Li2O is (0.01-0.5):(0.01-0.05):(0.003-0.01).

[0016] In the aluminum nitride ceramic slurry of the present invention, the mass ratio of aluminum nitride powder to Al-Y alloy is controlled within the above-mentioned range, which not only ensures that sufficient liquid phase is provided to drive densification, but also avoids the formation of an excessively thick low thermal conductivity layer at the grain boundaries by excessive sintering aids.

[0017] Preferably, the mass ratio of the aluminum nitride powder to the Al-Y alloy is 1:(0.2-0.3).

[0018] More preferably, the mass ratio of the aluminum nitride powder to the Al-Y alloy is 1:0.2.

[0019] Preferably, in the sintering aid, the mass ratio of the Al-Y alloy, CaO, and Li2O is 0.2:0.03:0.006.

[0020] In a preferred embodiment of the aluminum nitride ceramic slurry of the present invention, the organic additives include binders, dispersants, plasticizers and solvents; the mass ratio of the aluminum nitride powder to the binders, dispersants, plasticizers and solvents is 1:(0.1-0.24):(0.07-0.1):(0.1-0.15):(0.2-0.35).

[0021] Preferably, the mass ratio of the aluminum nitride powder to the binder, dispersant, plasticizer, and solvent is 1:0.1:0.08:0.12:0.3.

[0022] In a preferred embodiment of the aluminum nitride ceramic slurry of the present invention, the binder includes at least one of polyvinyl alcohol, polyvinyl butyral, ethyl cellulose, and polyacrylic acid resin; and / or, the dispersant includes at least one of phosphate ester, polyvinylpyrrolidone, polyacrylamide, and polyacrylic acid; and / or, the plasticizer includes at least one of polyvinyl glycol and dibutyl ester; and the solvent includes at least one of anhydrous ethanol, isopropanol, and butanone.

[0023] Preferably, the adhesive comprises polyvinyl butyral.

[0024] Preferably, the dispersant comprises polyacrylic acid.

[0025] Preferably, the plasticizer comprises polyethylene glycol.

[0026] Preferably, the solvent includes anhydrous ethanol and butanone.

[0027] More preferably, the mass ratio of the anhydrous ethanol to the butanone is 1:2.

[0028] Secondly, the present invention provides a method for preparing the aluminum nitride ceramic slurry, comprising the following steps: mixing the aluminum nitride powder, sintering aid, and organic additive, and dispersing them by ball milling to obtain the aluminum nitride ceramic slurry.

[0029] Thirdly, the present invention provides an aluminum nitride ceramic substrate made of the aluminum nitride ceramic slurry.

[0030] Fourthly, the present invention provides a method for preparing the aluminum nitride ceramic substrate, comprising the following steps: S1. The aluminum nitride ceramic slurry is cast into a green aluminum nitride blank. S2. Perform a debinding process on the aluminum nitride green blank; S3. The aluminum nitride green blank after debinding is sintered to obtain the aluminum nitride ceramic substrate.

[0031] In a preferred embodiment of the method for preparing the aluminum nitride ceramic substrate of the present invention, in step S2, the adhesive removal is carried out by heating to 500℃-650℃ in an air atmosphere at a heating rate of 5℃ / min-15℃ / min and holding at that temperature for 1h-3h.

[0032] Preferably, the glue removal is performed by heating the material to 600°C in air at a heating rate of 10°C / min and holding it at that temperature for 1 hour.

[0033] In a preferred embodiment of the method for preparing the aluminum nitride ceramic substrate of the present invention, in step S3, the sintering is carried out in a nitrogen atmosphere at a heating rate of 5℃ / min-15℃ / min to 1500℃-1820℃, and held at that temperature for 1h-3h.

[0034] Preferably, in step S3, the sintering is carried out in a nitrogen atmosphere, with the temperature increased to 1780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours.

[0035] Fifthly, the present invention provides the application of the aluminum nitride ceramic slurry and the aluminum nitride ceramic substrate in electronic packaging or heat dissipation devices.

[0036] Compared with existing technologies, the beneficial effects of this invention are as follows: First, the aluminum nitride ceramic substrate prepared by this invention using a sintering aid system containing Al-Y alloy exhibits significant improvements in flexural strength, density, and thermal conductivity, while maintaining excellent volume resistivity, achieving synergistic optimization of high thermal conductivity and high strength. Second, the Al-Y alloy in the aluminum nitride ceramic slurry of this invention can more thoroughly purify the aluminum nitride lattice and optimize the distribution of grain boundary phases, thereby obtaining a higher density ceramic body at a lower sintering temperature, with fewer internal pores and better grain bonding. Furthermore, the aluminum nitride ceramic substrate prepared by this invention has excellent comprehensive performance, meeting the stringent requirements of high-power electronic devices for efficient heat dissipation while possessing good mechanical reliability and electrical insulation characteristics. It can be widely used in high-end electronic packaging scenarios such as high-density semiconductor lighting, 5G communication RF modules, and new energy vehicle power devices, significantly improving the long-term operational stability and service life of the equipment. Detailed Implementation

[0037] To better illustrate the objectives, technical solutions, and advantages of this invention, the invention will be further described below with reference to specific embodiments. Those skilled in the art should understand that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0038] The following description, in conjunction with specific embodiments, illustrates the practical effects of the present invention.

[0039] Unless otherwise specified, the experimental methods used in the examples are conventional methods; the materials, reagents, equipment, etc. used are all commercially available unless otherwise specified.

[0040] The raw materials used in the following embodiments and comparative examples are described below, but are not limited to these materials: The preparation methods of the Al-Y alloy, Al-Sm alloy, and Al-Ti alloy of the present invention include the following steps: (1) Al metal with different mass ratios and an average particle size of 5 μm was mixed evenly with Y metal, Sm metal or Ti metal and then placed in a crucible; the crucible was placed in a vacuum induction melting furnace and evacuated to a vacuum degree of 10. -3 Pa, then high-purity argon gas is introduced as a protective atmosphere; repeat the above vacuuming-argon purging operation three times in total to fully remove residual air from the furnace; (2) The furnace temperature is raised to 900℃ and held for 2 hours to allow the metal powder to be completely melted and alloyed, forming Al-Y, Al-Sm or Al-Ti alloy blocks respectively. Finally, the obtained alloy blocks are crushed, air-flow milled and ball-milled for 8 hours to obtain Al-Y alloy, Al-Sm alloy or Al-Ti alloy with an average particle size of 0.5μm.

[0041] Example 1: This embodiment provides an aluminum nitride ceramic slurry, which comprises the following components in parts by weight: 1 part aluminum nitride powder; Sintering aids: 0.2 parts Al-Y alloy, 0.03 parts CaO, and 0.006 parts Li2O; wherein, in the Al-Y alloy, the mass ratio of Al to Y is 1:3; Adhesive: 0.1 parts polyvinyl butyral; Dispersant: 0.08 parts polyacrylic acid; Plasticizer: 0.12 parts of polyvinyl glycol; Solvent: 0.3 parts of a mixed solvent consisting of anhydrous ethanol and butanone; wherein the mass ratio of anhydrous ethanol to butanone is 1:2.

[0042] The preparation method of aluminum nitride ceramic slurry in this embodiment includes the following steps: The aluminum nitride powder, sintering aid, binder, dispersant, plasticizer and solvent in the above proportions were mixed and dispersed by ball milling. The ball milling process parameters were set as follows: a planetary ball mill was used, the revolution speed was 300 r / min, the ratio of the rotation speed to the revolution speed was 1:2 (i.e., the rotation speed was 150 r / min), and the total ball milling time was 20 h. After the ball milling was completed, aluminum nitride ceramic slurry was obtained.

[0043] Example 2-15: The only difference between Examples 2-15 and Example 1 is the composition and / or ratio of the aluminum nitride ceramic slurry, as shown in Tables 1 and 2: Table 1: Component ratios (parts by weight) of aluminum nitride ceramic slurries in Examples 1-9 of the present invention Table 2: Component ratios (parts by weight) of aluminum nitride ceramic slurries in Examples 1 and 10-15 of the present invention Comparative Example 1: The only difference between this comparative example and Example 1 is that it does not include the Al-Y alloy.

[0044] Comparative Example 2: The only difference between this comparative example and Example 1 is that the Al-Y alloy (0.2 parts) is replaced with Al metal (0.05 parts) and Y2O3 (0.19 parts) in amounts equal to Al and Y.

[0045] Comparative Example 3: The only difference between this comparative example and Example 1 is that the Al-Y alloy (0.2 parts) is replaced with an equal amount of Al metal (0.2 parts).

[0046] Comparative Example 4: The only difference between this comparative example and Example 1 is that the Al-Y alloy (0.2 parts) is replaced with an equal amount of Y metal (0.2 parts).

[0047] Comparative Example 5: The only difference between this comparative example and Example 1 is that the Al-Y alloy (0.2 parts) is replaced with an equal amount of mechanically mixed powder of Al metal and Y metal (0.2 parts); wherein the mass ratio of Al to Y is 1:3.

[0048] Comparative Example 6: The only difference between this comparative example and Example 1 is that the Al-Y alloy (0.2 parts) is replaced with a mixture of Al2O3 and Y2O3 in the same amount of substance as Al and Y (0.28 parts, based on the same amount of alloy oxidation).

[0049] Comparative Example 7: The only difference between this comparative example and Example 1 is that the Al-Y alloy (0.2 parts) is replaced with an equal amount of Al-Sm alloy (0.2 parts); wherein the mass ratio of Al to Sm is 1:3.

[0050] Comparative Example 8: The only difference between this comparative example and Example 1 is that the Al-Y alloy (0.2 parts) is replaced with an equal amount of Al-Ti alloy (0.2 parts); wherein the mass ratio of Al to Ti is 1:3.

[0051] Application Example 1: This application example provides an aluminum nitride ceramic substrate, the preparation method of which includes the following steps: (1) Casting: The aluminum nitride ceramic slurry of Example 1 was cast to obtain aluminum nitride green body; (2) Debinding: The obtained aluminum nitride green blank is placed in an air atmosphere and heated to 600℃ at a heating rate of 10℃ / min, and kept at the temperature for 1h to remove the organic components therein; (3) Sintering: The aluminum nitride green blank after debinding is placed in a nitrogen atmosphere and heated to 1780°C at a heating rate of 10°C / min. It is held for 2 hours and then cooled in the furnace to obtain an aluminum nitride ceramic substrate.

[0052] Application Examples 2-15: The only difference between Application Examples 2-15 and Application Example 1 is that the aluminum nitride ceramic slurry used in Example 1 is replaced with the aluminum nitride ceramic slurry used in Example 2-15.

[0053] Application Comparative Examples 1-8: The only difference between Comparative Examples 1-8 and Application Example 1 is that the aluminum nitride ceramic slurry used in Example 1 is replaced with the aluminum nitride ceramic slurry used in Comparative Examples 1-8.

[0054] Test example: The following performance tests were performed on the aluminum nitride ceramic substrates prepared in Application Examples 1-15 and Comparative Examples 1-8 of the present invention, and the test results are summarized in Table 3.

[0055] (1) Bending strength test Test method: The bending strength of each aluminum nitride ceramic substrate was tested according to the three-point bending method. The test conditions were: span 30 mm, loading rate 0.05 mm / min, sample size 40 mm × 24 mm × 0.38 mm, and the test was carried out using a universal testing machine.

[0056] (2) Thermal conductivity test Test method: The thermal conductivity of each aluminum nitride ceramic substrate at room temperature was tested using a thermal conductivity meter and the laser flash method.

[0057] (3) Density test Test method: The actual density of each aluminum nitride ceramic substrate was tested using Archimedes' water displacement method based on Archimedes' principle.

[0058] (4) Volume resistivity test Test method: The volume resistivity of each aluminum nitride ceramic substrate was tested according to the method specified in the national standard GB 5594.5-1985 "Test Method for Performance of Structural Ceramic Materials for Electronic Components - Test Method for Volume Resistivity".

[0059] Table 3: Performance test results of aluminum nitride ceramic substrates in the test examples of this invention As can be seen from the results in Table 3, the aluminum nitride ceramic substrates prepared by the aluminum nitride ceramic slurry of the present invention are significantly superior to the comparative examples in key performance indicators such as flexural strength, thermal conductivity, density, and volume resistivity, exhibiting excellent comprehensive performance. Specifically, in terms of flexural strength, the aluminum nitride ceramic substrates prepared by the aluminum nitride ceramic slurry of Examples 1-15 of the present invention all reach above 380 MPa, with the highest reaching 401 MPa, while the flexural strength of Comparative Examples 1-8 is only 350-371 MPa. This indicates that the alloy powder prepared by the present invention using Al-Y alloy as a sintering aid and through vacuum induction melting combined with ball milling can effectively promote the densification sintering of aluminum nitride ceramics, while forming a uniformly distributed grain boundary phase, reducing structural defects, and significantly improving the mechanical strength of the material.

[0060] Secondly, regarding thermal conductivity, the aluminum nitride ceramic substrates prepared by the aluminum nitride ceramic slurry in Examples 1-15 of this invention have a thermal conductivity range of 180-192 W / (m·K), with Example 7 reaching 192 W / (m·K), while the thermal conductivity of all comparative examples does not exceed 175 W / (m·K). This means that by introducing an Al-Y alloy and combining it with CaO and Li2O composite sintering aids, this invention can effectively reduce and remove oxygen impurities in the AlN lattice, while forming a low thermal resistance grain boundary phase, reducing phonon scattering, thereby obtaining a higher measured thermal conductivity. In contrast, Comparative Example 2, which used a combination of Al metal and Y2O3, Comparative Example 3, which used only Al metal, and Comparative Example 4, which used only Y metal, all failed to form a uniform alloying active component, resulting in low thermal conductivity. Comparative Examples 7 and 8, which used Al-Sm alloy and Al-Ti alloy to replace Al-Y alloy, respectively, also had thermal conductivity of only 171-172 W / (m·K). This further demonstrates that the Y element in the Al-Y alloy of this invention has unique advantages in promoting AlN lattice purification and grain boundary phase optimization.

[0061] Furthermore, regarding density, the aluminum nitride ceramic substrates prepared from the aluminum nitride ceramic slurry of Examples 1-15 of this invention have a density of 3.3-3.5 g / cm³. 3 The density is close to the theoretical density of AlN, while the density of the comparative example is only 3.1 g / cm³. 3 Higher density means fewer pores and better grain bonding, which not only improves thermal conductivity but also enhances bending strength. In the embodiments of this invention, the addition of Al-Y alloy promotes particle rearrangement and mass migration during liquid phase sintering, thereby achieving high material density.

[0062] Furthermore, in terms of volume resistivity, the aluminum nitride ceramic substrates prepared by the aluminum nitride ceramic pastes in Examples 1-15 of this invention all reach 2.7 × 10⁻⁶. 12The resistivity is above Ω·cm, fully meeting the stringent requirements for high insulation in electronic packaging materials; while the volume resistivity of Comparative Examples 1-7 is 2.4-2.6×10⁻⁶. 12 The volume resistivity of Comparative Example 8 decreased sharply to 0.1 × 10⁻⁶ Ω·cm, slightly lower than that of the Example 8. 12 The Ω·cm is because the introduction of Ti element will form a conductive phase at the grain boundary or cause free electrons to be generated in the lattice, which will seriously degrade the insulation performance. This further confirms the key role of Y element selected in this invention in maintaining excellent electrical insulation properties.

[0063] In summary, this invention optimizes the composition of sintering aids and their alloying preparation methods, and coordinates with binders, dispersants, plasticizers, and solvent systems to obtain aluminum nitride ceramic substrates with high flexural strength, high thermal conductivity, high density, and high volume resistivity after casting, debinding, and sintering. This allows the substrates to significantly improve heat dissipation efficiency and mechanical reliability in high-end applications such as high-power electronic packaging, high-density semiconductor lighting (LEDs), 5G communication RF modules, and new energy vehicle power devices. It also significantly improves the lifespan and long-term operational stability of electronic components, demonstrating highly competitive application prospects and industrialization value in the fields of high heat flux density electronic heat dissipation and high-reliability packaging.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. An aluminum nitride ceramic slurry, characterized in that, It includes aluminum nitride powder, sintering aids and organic additives; the sintering aids include Al-Y alloy; in the Al-Y alloy, the mass ratio of Al to Y is 1:(0.2-5).

2. The aluminum nitride ceramic slurry as described in claim 1, characterized in that, In the Al-Y alloy, the mass ratio of Al to Y is 1:(1.5-5).

3. The aluminum nitride ceramic slurry as described in claim 1, characterized in that, The Al-Y alloy is produced by mixing Al metal and Y metal, followed by vacuum induction melting and ball milling in a high-purity argon atmosphere.

4. The aluminum nitride ceramic slurry as described in claim 1, characterized in that, The mass ratio of the aluminum nitride powder to the Al-Y alloy is 1:(0.01-0.5); and / or, the sintering aid further includes CaO and Li2O; the mass ratio of the Al-Y alloy, CaO, and Li2O is (0.01-0.5):(0.01-0.05):(0.003-0.01).

5. The aluminum nitride ceramic slurry as described in claim 1, characterized in that, The organic additives include binders, dispersants, plasticizers, and solvents; the mass ratio of the aluminum nitride powder to the binders, dispersants, plasticizers, and solvents is 1:(0.1-0.24):(0.07-0.1):(0.1-0.15):(0.2-0.35).

6. The aluminum nitride ceramic slurry as described in claim 5, characterized in that, The binder includes at least one of polyvinyl alcohol, polyvinyl butyral, ethyl cellulose, and polyacrylic acid resin; and / or the dispersant includes at least one of phosphate ester, polyvinylpyrrolidone, polyacrylamide, and polyacrylic acid; and / or the plasticizer includes at least one of polyethylene glycol and dibutyl ester; the solvent includes at least one of anhydrous ethanol, isopropanol, and methyl ethyl ketone.

7. The method for preparing the aluminum nitride ceramic slurry according to any one of claims 1-6, characterized in that, The process includes the following steps: mixing the aluminum nitride powder, sintering aid, and organic additive, and then dispersing them by ball milling to obtain the aluminum nitride ceramic slurry.

8. An aluminum nitride ceramic substrate, characterized in that, It is made from the aluminum nitride ceramic slurry as described in any one of claims 1-6.

9. The method for preparing the aluminum nitride ceramic substrate according to claim 8, characterized in that, Includes the following steps: S1. The aluminum nitride ceramic slurry is cast into a green aluminum nitride blank. S2. Perform a debinding process on the aluminum nitride green blank; S3. The aluminum nitride green blank after debinding is sintered to obtain the aluminum nitride ceramic substrate.

10. The application of the aluminum nitride ceramic slurry according to any one of claims 1-6 and the aluminum nitride ceramic substrate according to claim 8 in electronic packaging components or heat dissipation devices.